Tests to evaluate the workability of Alnus nepalensis D. Don wood - Merino López , Jonathan Alexis (2023)
The study was conducted at the Wood Center of the National University of Loja with the aim of evaluating the workability of Alnus nepalensis D. Don wood (alder) through planing, sanding, drilling, and turning tests, according to the standards established in ASTM-D 1999.87 (ASTM, 1999). The test specimens were subjected to two drying conditions, a program of outdoor air drying and another under controlled conditions in a solar dryer. The specimens were dried for 90 days, and the results showed that the moisture content is significantly different between the two drying programs, resulting in 7.85% for the solar dryer specimens and 14.12% for the specimens dried in open air. With regard to wood workability, the specimens exhibited torn and lifted grain during planing. Sanding resulted in a smooth surface without scratching defects or fuzzy grain. Drilling yielded better results using a metal drill bit, and turning showed defects due to torn grain, resulting in a rough texture. In conclusion, there is no significant difference in workability results between specimens with different moisture contents, possibly due to the species being of medium density (0.46 g/cm3). Therefore, it is highly recommended for carpentry, joinery, and simple structures.